Pelaksanaan E-government melalui Online Single Submission Risk Based Approach (OSS RBA) di DPMPTSP Kabupaten Indragiri Hulu - Linda Lestari; Zulkarnaini Zulkarnaini (Jurnal Ilmiah Wahana Pendidikan, 2023)
Online Single Submission Risk Based Approach (OSS RBA) is a risk-based business permit implementation program which is an improvement over the previous OSS, namely OSS version 1.1 with the aim of simplifying and accelerating the business permit process based on Government Regulation Number 5 of 2021 concerning the Implementation of Risk-Based Business Licensing.The purpose of this study is to find out and analyze the implementation of e-government through the RBA OSS in the DPMPTSP of Indragiri Hulu Regency, as well as obstacles in its implementation. The theoretical concept used by researchers is the theory of elements of successful implementation of E-government by Indrajit (2016: 11), namely the Support, Capacity and Value elements. This research is a qualitative descriptive research. With data analysis including data reduction, data presentation, and conclusions. The results in this study show that the implementation of the RBA OSS in the DPMPTSP of Indragiri Hulu Regency went well and was successfully carried out based on government support, especially the DPMPTSP of Indragiri Hulu Regency, available capabilities or capacities such as supporting infrastructure and expert and competent human resources, as well as benefits that are not only felt by the government, but also felt in business actors / applicants. The inhibiting factor in its implementation is the low human resources of the RBA OSS program and the system managed by the OSS institution is still in the stage of improvement.